STUDENTS’ GRAMMATICAL PROBLEMS IN DEVELOPING THE PARAGRAPHS OF ARGUMENTATIVE ESSAY - Riyen Permata (Universitas Mahaputra Muhammad Yamin, 2022)
This research aimed to determine the grammatical problems found in students’ argumentative essays. The type of research used was descriptive research and the data source of this research was argumentative essays written by English Department students. Research data were collected by giving writing assignments and coding sheets. The collected data were grouped based on the research objectives, then described and analyzed to get the actual facts. The research findings showed that some of the grammatical problems that were often faced by students in writing argumentative essays were subject-predicate compatibility, verb forms, verb tenses, plural forms, and word formation errors as well as problems in the use of conjunctions, auxiliary modals and the use of personal subjects. In conclusion, the students still do not understand the concept of grammar well, and it will be difficult for them to produce a good argumentative essay.